2006
DOI: 10.1021/es0613512
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment, Performance, and Microbial Diversity of a Thermophilic Mediatorless Microbial Fuel Cell

Abstract: A thermophilic mediatorless microbial fuel cell (ML-MFC) was developed for continuous electricity production while treating artificial wastewater concurrently. A maximum power density of 1030 +/- 340 mW/m2 was generated continuously at 55 degrees C with an anode retention time of 27 min (11 mL h(-1)) and continuous pumping of air-saturated phosphate buffer into the cathode compartment at the retention time of 0.7 min (450 mL h(-1)). Meanwhile, about 80% of the electrons available from acetate oxidation were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(93 citation statements)
references
References 28 publications
7
83
2
1
Order By: Relevance
“…Two Gram-positive phyla, Firmicutes (11 OTUs, 234 clones, 79% of clones) and Coprothermobacteria (two OTUs, 48 clones, 16% of clones), represented 95% of the clone sequences. Coprothermobacter species were previously identified by culture-independent molecular techniques in an MFC study with acetate as an electron donor and a thermophilic anaerobic digester inoculum (Jong et al, 2006). In that study, Coprothermobacter sequences represented 15.1% of the community.…”
Section: Dominant Bacterial Species Identifiedmentioning
confidence: 91%
See 2 more Smart Citations
“…Two Gram-positive phyla, Firmicutes (11 OTUs, 234 clones, 79% of clones) and Coprothermobacteria (two OTUs, 48 clones, 16% of clones), represented 95% of the clone sequences. Coprothermobacter species were previously identified by culture-independent molecular techniques in an MFC study with acetate as an electron donor and a thermophilic anaerobic digester inoculum (Jong et al, 2006). In that study, Coprothermobacter sequences represented 15.1% of the community.…”
Section: Dominant Bacterial Species Identifiedmentioning
confidence: 91%
“…This is further supported by culture-independent studies, which indicate that the phylogenetic diversity of MFC microbial communities far exceeds that of electrochemically active isolates. Unfortunately, these community studies (Bond et al, 2002;Lee et al, 2003;Holmes et al, 2004;Kim et al, 2004;Rabaey et al, 2004;Aelterman et al, 2006;Jong et al, 2006;Kim et al, 2006) were hampered by the use of lowresolution DNA fingerprinting techniques targeting the 16S ribosomal RNA gene (16S rDNA), the presence of which does not necessarily demonstrate electrochemical activity but may simply be an artifact of gene persistence in the environment (Manefield et al, 2002). Furthermore, because these studies focused on gene presence (16S rDNA) rather than gene expression (16S rRNA) they could not elucidate active members of the anode biofilm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applied Biosytems 2720 Thermal Cycler was used for PCR and set at the following parameters: initial denaturation at 95°C for 3 min, followed by 35 cycles of denaturation (30 s at 94°C), annealing (45 s at 60°C and extension, 90 min at 72°C) and a final extension at 72°C for 7 min before storage at -4°C. The products were electrophoresed on an agarose gel to confirm their presence, quality and purity (Jong et al, 2006).…”
Section: Pcr-amplificationmentioning
confidence: 99%
“…8) Several studies have shown that thermophilic MFCs, which are inoculated with thermophilic microorganisms (with optimal growth temperature between 45 and 80°C), exhibit good performance at operating temperatures approximately 55-60°C. 6,[9][10][11][12][13] However, compared to mesophilic systems, MFCs with higher operation temperatures remain underexploited. For example, exoelectrogenic activity has been reported in more than 20 bacterial species, but most are mesophilic species affiliated with the phylum Proteobacteria.…”
mentioning
confidence: 99%